What shapes social attitudes toward corruption in China? Micro-level evidence - Zuzana Fungáčová; Ilari Määttä; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This research investigates the determinants of corruption in China using micro-level data. We use survey data on 6,000 households from 28 provinces to estimate logit models that show how corruption perceptions and attitudes to corruption are shaped by individual and provincial determinants. Respondents who see themselves as lower class, as well as members of the Communist Party of China, are more likely to perceive and reject corruption than other respondents. People in rural areas perceive less corruption, but do not differ in their attitudes toward corruption.
URN:NBN:fi:bof-201612131529
Keywords: H11; K42; P16; 330